2015
DOI: 10.1074/jbc.m115.648352
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Vaccinia Virus Uracil-DNA Glycosylase in Complex with DNA

Abstract: Background: D4 is a uracil-DNA glycosylase (UNG) and an essential component of the vaccinia virus DNA polymerase holoenzyme. Results: The crystal structure of D4 in complex with DNA is presented. Conclusion: The D4⅐DNA contacts exhibit major differences compared with the human UNG⅐DNA complex. Significance: This work allows a better understanding of the structural determinants required for UNG function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 50 publications
(62 reference statements)
1
49
0
Order By: Relevance
“…Protein-protein interactions, in addition to protein-DNA interactions, may contribute to the association of these proteins with nascent DNA. For example, D4 can bind DNA (87,88) and, together with A20 (which has not been shown to bind DNA) and E9, forms a holoenzyme complex (23). H5 has affinity for DNA and interacts with both A20 (77) and the B1 protein kinase (77,89).…”
Section: Discussionmentioning
confidence: 99%
“…Protein-protein interactions, in addition to protein-DNA interactions, may contribute to the association of these proteins with nascent DNA. For example, D4 can bind DNA (87,88) and, together with A20 (which has not been shown to bind DNA) and E9, forms a holoenzyme complex (23). H5 has affinity for DNA and interacts with both A20 (77) and the B1 protein kinase (77,89).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, D4 shares only ~ 20% sequence identity with human and E. coli uracil DNA glycosylases (Schormann et al, 2013; Schormann et al, 2007) and is resistant to the UGI protein, a well-studied inhibitor of many prokaryotic and eukaryotic UDGs (Ellison et al, 1996). D4 has been the subject of numerous crystallography studies (see below), the results of which have revealed that despite the limited primary amino acid sequence homology to other Family I UDGs, the structure of the VACV protein adopts the characteristic alpha / beta fold of DNA glycosylases (Burmeister et al, 2015; Contesto-Richefeu et al, 2014; Schormann et al, 2013; Schormann et al, 2007). …”
Section: Assembly Of a Processive Holoenzyme: The A20 And D4 (Udg)mentioning
confidence: 99%
“…Several groups have undertaken a detailed investigation of the protein structure of D4 alone, in complex with the N′-terminus of A20 and/or in complex with DNA oligonucleotides (Burmeister et al, 2015; Contesto-Richefeu et al, 2014; Contesto-Richefeu et al, 2016; Sartmatova et al, 2013; Schormann et al, 2013; Schormann et al, 2015; Schormann et al, 2007). In 2007, the first crystal structure of the D4 uracil DNA glycosylase was published (Schormann et al, 2007).…”
Section: : Structural Analysis Of the D4 D4/dna D4/a20 D4/a20/dnamentioning
confidence: 99%
“…Surface plasmon resonance (SPR) experiments were carried out on a Biacore 3000 instrument (GE Healthcare) using CM5 sensor chips with immobilized streptavidin to which the 5=-end-biotinylated primer 5=-CCG AAT CAG GAA GAT AAC AGC GGT TTA GCC-3= was bound directly or after annealing to the complementary sequence as described previously (33). Experiments were performed in the appropriate gel filtration buffers described above at a flow rate of 15 l/min.…”
Section: Sprmentioning
confidence: 99%